Effect of gamma irradiation on the technological properties of mixed starch of turmeric´s primary and secondary rhizomes (Research, Society and Development, 2023)
This study aimed to evaluate the effect of irradiation on technological properties of mixed starches extracted from primary and secondary rhizomes of turmeric. Was used Mara Rosa city´s tumeric, Goiás State, for the extraction of mixed starches by the method of decanting. The extracted starches were subjected to radiation doses of 2.5, 5 and 10kGy, except the control was not irradiated. Subsequently, they were subjected to the following tests: scanning electron microscopy; thermal properties; X-ray diffraction; swelling power and solubility in water. The irradiation did not influence the morphology of the starch granules, however, it may have caused changes in molecular level. The starches irradiated and control showed B type diffraction pattern, irradiation decreased the crystallinity of treated starches, but increased in the sample irradiated with 5kGy. The gelatinization temperatures of the samples were not affected by irradiation, however, reduced the enthalpy of gelatinization of the irradiated starches. The water solubility increased with increasing radiation dose. The swelling power of the irradiated samples was reduced compared to control. Technological changes induced by gamma irradiation allow the mixed starch potential applications in the food industries.